Proses Seleksi Hakim Konstitusi: Problematika dan Model Ke Depan - Timbo Mangaranap Sirait (The Constitutional Court of the Republic of Indonesia, 2021)
The disparity in the selection mechanism of the Constitutional Court Judge has led to a trifurcation to the selection of constitutional judges carried out by the President, the House of Representatives, and the Supreme Court. The trifurcation of the Constitutional Court judge selection can not be separated from the construction of norms in the Constitutional Court Law which regulates the constitutional judge selection that have a high degree of flexibility so that they can be interpreted freely and suit the tastes of each regime by the institutions that have the constitutional authority to propose constitutional judge. The problem in this research is show to implementation of the selectionsystem of constitutional judgesin Indonesiais currently and how the model of selection of constitutional judges will be the future. The analysis will be carried out normatively using a statutory, historical and conceptual approach. The results of the study show that the redesign of the constitutional Court Judge selection is an urgent matter to establish the standards of the Constitutional Court judge selection valuation in a transparent, participatory, objective, and accountable manner. The recruitment and selection model for Constitutional Court judges that using a selection panel either by the respective Constitutional Judges Proposing institutions or by the form of an agreement of the respective constitutional judge proposing institutions is a legal reform that have a main goal which is to produce the constitutional court judges who have ideal integrity as a true statesman. The recruitment process using a clear and standard selection panel is a fulfillment of the main principles of the constitutional judge position filling mandated by the Constitutional Court Law.